A Comprehensive Analysis of Hydrolyzed Collagen Supplementation Effects on Skin Aging and Texture and Its Potential Benefits for Osteoarthritis - Khan, Muhammad Ammar (Indus Journal of Bioscience Research, 2025)
Background: Hydrolyzed collagen supplementation has gained popularity for its potential to improve skin health and combat signs of aging. This study investigates its effects on skin elasticity, hydration, and texture over a 12-week intervention period. Objective: To evaluate the efficacy of hydrolyzed collagen supplementation in reducing visible signs of skin aging and improving overall skin health and its potential benefits for osteoarthritis. Methods: A randomized, double-blind, placebo-controlled study was conducted with 55 participants aged 25–60 years from March 2024 to September 2024. The treatment group received 10 grams of hydrolyzed collagen daily, while the placebo group received an identical placebo. Skin elasticity, wrinkle depth, and hydration were assessed using objective tools, and self-reported improvements were collected through surveys. Results: The treatment group demonstrated significant improvements, including a 23% increase in skin elasticity (p<0.01), an 18% reduction in wrinkle depth (p<0.05), and a 28% increase in skin hydration (p<0.01). Self-assessment revealed 82% of participants in the treatment group perceived noticeable improvements compared to 33% in the placebo group. Conclusion: It is concluded that hydrolyzed collagen supplementation significantly improves signs of skin aging and offers measurable relief from osteoarthritis symptoms. Its dual benefits make it a promising non-pharmacological option for individuals seeking combined dermatologic and musculoskeletal health support.